Mechanisms of HIV-immunologic non-responses and research trends based on gut microbiota - Xiangbin Sun; Zhanpeng Xie; Zhen Wu; Meiyang Song; Youxian Zhang; Zezhan Zhang; Xinxin Cui; Aodi Liu; Ke Li (Frontiers in Immunology)
With the increasing number of people with HIV (PWH) and the use of antiretroviral treatment (ART) for PWH, HIV has gradually become a chronic infectious disease. However, some infected individuals develop issues with immunologic non-responses (INRs) after receiving ART, which can lead to secondary infections and seriously affect the life expectancy and quality of life of PWH. Disruption of the gut microbiota is an important factor in immune activation and inflammation in HIV/AIDS, thus stabilizing the gut microbiota to reduce immune activation and inflammation and promoting immune reconstitution may become a direction for the treatment of HIV/AIDS. This paper, based on extensive literature review, summarizes the definition, mechanisms, and solutions for INRs, starting from the perspective of gut microbiota.